Contributing factors to underweight among children under five: A cross-sectional study at Belawan Primary Health Center - Endang Sihaloho; Antonij Edimarta Sitanggang (AcTion: Aceh Nutrition Journal, 2025)
Underweight in toddlers is a significant public health concern in Indonesia, where the 2022 National Nutrition Status Survey reported a prevalence of 17,1% among children under five years of age, reflecting persistent nutritional challenges. This study aimed to analyze the incidence of underweight in toddlers in the Belawan Primary Health Center (PHC) and its contributing factors. This research applied a descriptive-analytical design with a cross-sectional approach, conducted in January 2025, in Belawan, Medan City, North Sumatra. A total of 41 toddlers were selected using a total sampling method. Data were collected using structured questionnaires and secondary records, and ethical approval was obtained from the Institutional Review Board. The sample size was determined based on the population of underweight toddlers recorded at the health center. Data were analyzed using chi-square tests and logistic regression. The results indicated significant associations between exclusive breastfeeding (p=0,032), inappropriate complementary feeding (p=0,041), and maternal education (p=0,021) and underweight incidence. Logistic regression showed that low maternal education was the most dominant factor (OR=7,26). In conclusion, the role of mothers is very important in child feeding practices. Interventions to reduce underweight should prioritize maternal education and community-based nutrition programs by strengthening the roles of health workers and Integrated Health Post cadres.